Entry and exit in treasury auctions - Jason Allen; Ali Hortaçsu; Eric Richert; Milena Wittwer (Bank of Canada, 2024)
Many financial markets are populated by dealers, who commit to participate regularly in the market, and non-dealers, who do not commit. This market structure introduces a trade-off between competition and volatility, which we study using data on Canadian treasury auctions. We document a consistent exit trend by dealers and increasing, but irregular, participation by non-dealer hedge funds. Using a structural model, we evaluate the impact of dealer exit on hedge fund participation and its consequences for market competition and volatility. We find that hedge fund entry was partially driven by dealer exit, and that gains thanks to stronger competition associated with hedge fund entry are offset by losses due to the irregular market participation of hedge funds. We propose an issuance policy that stabilizes hedge fund participation at a sufficiently high average level and achieves revenue gains.
Keywords: D44; D47; G12; G28; 330; Debt management; Financial markets; Financial institutions; Market structure and pricing